The Role of Active Breaks and Curriculum-Based Active Breaks in Enhancing Executive Functions and Math Performance, and in Reducing Math Anxiety in Primary School Children: A Systematic Review - Rosa Bellacicco; Francesca Capone; Clarissa Sorrentino; Valeria Di Martino (Education Sciences)
Physical activity is recognized as crucial for children’s development in many aspects. However, its integration into the classroom remains a challenge, particularly in STEM subjects, despite this area being a central component of school curricula worldwide. This systematic review investigates the characteristics and the relationships between active breaks (AB) and curriculum-based active breaks (CB) interventions on executive functions, attention, on-task behavior, performance in STEM, and math anxiety in primary school children. A database search, following the PRISMA 2020 guidelines, was conducted in March 2024, identifying 19 eligible studies for descriptive analysis and assessed for risk of bias. A total of 13 studies focused on AB, four on CB, and two compared the two conditions. Only one paper considered math anxiety. The results revealed mixed effects on executive functions and attention, with some studies reporting improvements and others finding no significant changes. Math performance improved with both AB and CB interventions, especially when AB lasted 10 to 20 min. Most interventions were led by teachers, though few studies incorporated intervention fidelity. Overall, the inconsistent findings highlight the need for further research to determine the optimal characteristics for effective interventions and reliable assessment methods and to explore long-term effects and the appropriate level of teacher involvement.